2014
DOI: 10.1177/1753465814547517
|View full text |Cite
|
Sign up to set email alerts
|

Omalizumab: a new treatment option for allergic bronchopulmonary aspergillosis in patients with cystic fibrosis

Abstract: Background: Allergic bronchopulmonary aspergillosis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 24 publications
0
32
2
Order By: Relevance
“…Omalizumab has also demonstrated its clinical relevance in patients with allergic bronchopulmonary aspergillosis (ABPA), an allergic reaction to Aspergillus characterized by high IgE levels, which usually occurs in combination with cystic fibrosis (CF) [86, 87]. Several case series have also reported success with OmAb in ABPA patients without CF [88, 89].…”
Section: Anti-ige-based Treatmentsmentioning
confidence: 99%
“…Omalizumab has also demonstrated its clinical relevance in patients with allergic bronchopulmonary aspergillosis (ABPA), an allergic reaction to Aspergillus characterized by high IgE levels, which usually occurs in combination with cystic fibrosis (CF) [86, 87]. Several case series have also reported success with OmAb in ABPA patients without CF [88, 89].…”
Section: Anti-ige-based Treatmentsmentioning
confidence: 99%
“…However, the ideal treatment duration of Omalizumab for ABPA is still ambiguous; Richard B. Moss (2012) reported a case of Omalizumab use as long as 5 years wherein an attempt to discontinue Omalizumab in late 2010 resulted in an exacerbation, decline in lung function, and rise in IgE levels, which were resolved with reinstitution of Omalizumab [39]. Sylvia L.et al (2014) also reported two subjects that experienced exacerbation after Omalizumab withdrawal [46].…”
Section: Discussionmentioning
confidence: 99%
“…However, the experience cases reported lacked a comparison, placebotreated group. Lehmann et al published their experience with omalizumab in six patients with CF and ABPA, and all patients showed an improvement, but omalizumab therapy was less effective in patients with progressed lung disease and long-term ABPA [27]. Finally, Jat et al published a Cochrane review about anti-IgE therapy for ABPA in CF patients and authors concluded that there is lack of evidence for the efficacy of omalizumab therapy in patients with CF and ABPA [28].…”
Section: Allergic Bronchopulmonary Aspergillosismentioning
confidence: 92%